(untitled) (IASH Indian Journal of Arid Horticulture, 2025)
Khadrawy, Saidy and Shamran are three significant date palm cultivars grown in Jaisalmer, Rajasthan, located in the North Western part of India. These cultivars are primarily consumed in their dried form, known as Chhuhara, during the Doka stage of fruit maturity. Climatic factors, including temperature, relative humidity, and sunshine hours, play a critical role in spathe initiation and opening in both male and female palms. The data on date to first spathe and its opening in the palm was recorded in the three cultivars consecutively for 6 years from 2008-2013 from 25 Years old plantation located at Chandan Experimental farm of ICAR-Central Arid Zone Research Zone, Regional Research Station, Jaisalmer and correlation was studied with three climatic parameter i.e. temperature, relative humidity and sunshine hours. The investigation revealed that significant effect of temperature (male-3.99e-07**, female-2.05e-08***), relative humidity (male-0.000236***, female-0.00237**) and sunshine hours (male-0.015550*, female-0.01649*) on days taken to first opening of spathe in both the sexes of the palm. Higher relative humidity extends the time required for male spathes to open, while lower humidity levels accelerate the process. This observation highlights the need to investigate the underlying mechanisms and potential interactions between these environmental factors to better understand their influence on spathe development.